NLRP3 Inflammasome From Bench to Bedside: New Perspectives for Triple Negative Breast Cancer - Sonnessa, Margherita; Cioffi, Antonella; Brunetti, Oronzo; Silvestris, Nicola; Zito, Francesco A.; Saponaro, Concetta; Mangia, Anita (Frontiers in Oncology, 2020)
Tumor microenvironment (TME) is crucial in cancer onset, progression, and response to treatment. It is characterized by an intricate interaction of immune cells and cytokines involved in tumor development. Among these, inflammasomes are oligomeric molecular platforms and play a crucial role in inflammatory response and immunity. Inflammasomes activation starts from the triggering of the pattern recognition receptors, Toll-like receptors, NOD-like receptors, and Absent in melanoma like receptors, on the surface of immune cells with the recruitment of caspase-1 by adaptor apoptosis-associated speck-like protein. This structure leads to the activation of pro-inflammatory cytokines interleukin (IL)-1β and IL-18 and participates in different biological processes exerting its effects. To date, Nod–Like Receptor Protein 3 (NLRP3) inflammasome has been deeply studied, revealing its involvement in different cancer diseases. In this review, an overview regarding the structure, biology, and mechanisms of inflammasomes is discussed. In addition, we focused on the specific role of NLRP3 in breast cancer and in the sub-group of triple negative breast cancer. NLRP3 inflammasome and its down-stream pathways could be considered new possible tumor biomarkers and could open new frontiers in breast cancer treatment.